Efecto de tiempos de imbibición y soluciones aplicadas en el priming sobre el comportamiento germinativo de semillas de coriandro - Bazzigalupi, Omar; Font, Ana Elisa; Llera, Alvaro; Aquilano, Claudio Gabriel (2017)
Coriander produces seeds with heteregeneous maturity range at harvest and long germination period. The priming is a technique to improve speed and uniformity of germination. Were evaluated effects on germination of seed in two trials: 1. Varying preimbibition time: 0, 5, 48 and 144 hours and 2. Type of solutions: KNO3 (0.2 %); NaCl (-1 MPa); gibberellic acid (200 mg·L-1); deionized water and witness without priming. Depending on the treatment, the seeds were imbibited on paper, at 20 °C and darkness, and then dried up to 10-11 % of moisture. Twenty days later they were sown on paper, at 20 °C with 8 hours a day of light. In both trials, four repetitions of 100 seeds were used for treatment, completely randomized design, analysis of variance and comparison of means of treatment according to Tukey (P ≤ 0.05). Every 24 hours seeds with emitted radicle were extracted. The index of germination speed (IVG), the percentage and the average time of germination (TMG) were calculated. With 48 to 144 hours of priming, the germination of the seeds began to 72 hours, with maximum rate to 120 and 96 hours respectively. The percentage of germination of 336 hours had no differences in times of hydropriming. Imbibition time of 48 hours presented the largest IVG and germinated 50 % of seeds two days in advance compared to the witness. The percentage of germination of seeds without priming had no difference with priming with KNO3 and water treatments. Gibberellic acid increases the IVG and the percentage of germination of coriander seeds. According to these results, we encourage the development of technologies of application of priming on coriander seeds to achieve greater speed and efficiency of establishment.